1995
DOI: 10.1111/j.1464-410x.1995.tb07386.x
|View full text |Cite
|
Sign up to set email alerts
|

Early catheter removal: a prospective study of 100 consecutive patients undergoing transurethral resection of the prostate

Abstract: Brief catheter drainage after TURP is safe and allows an earlier discharge from hospital than the standard duration of catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 7 publications
(1 reference statement)
4
21
0
Order By: Relevance
“…chronic obstructive pulmonary disease or chronic arterial disease) which would increase the anaesthetic risk or affect the course of hospital stay after surgery. The mean age of patients was 62.4 years, lower than that in previous studies because of selection bias in favour of younger patients (Table 1) [6–9,13–15].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…chronic obstructive pulmonary disease or chronic arterial disease) which would increase the anaesthetic risk or affect the course of hospital stay after surgery. The mean age of patients was 62.4 years, lower than that in previous studies because of selection bias in favour of younger patients (Table 1) [6–9,13–15].…”
Section: Discussionmentioning
confidence: 73%
“…Attempts at early catheter removal, and thus conducting TURP as day‐care surgery, have been underway since 1991 [7–9]. The concept of TURP in an outpatient setting has been possible through improvements in instrumentation, anaesthetic management during and after surgery, and increased experience with outpatient transurethral surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Early catheter removal after transurethral surgery has been practised in a number of reports and attempts have been made to determine the safety and efficacy of this approach [2][3][4][5][6][7][8]. Studies reported that, in certain patients with certain requirements, early catheter removal did not increase morbidity but reduced hospital stay and as a result the cost of TURP [2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts have been made to determine the feasibili- ty and safety of this approach. Catheter removal on postoperative day 2, on postoperative day 1 and day-case prostatectomy have been found to be applicable to some extent in a group of patients with certain requirements [2][3][4][5][6][7][8]. Though results are encouraging, we need more data to address this issue.…”
Section: Introductionmentioning
confidence: 96%
“…The predominant complication in previous studies was reinsertion of the catheter, which was required in 12-14% of patients in one study by Dodds et al .,[15] and 17.5% in another by Gordon. No patient in series of Chander et al .,[9] required reinsertion of the catheter after removal.…”
Section: Discussionmentioning
confidence: 99%